The After-Effects of Theta Burst Stimulation Over the Cortex of the Suprahyoid Muscle on Regional Homogeneity in Healthy Subjects - Ruan, Xiuhang; Zhang, Guoqin; Xu, Guangqing; Gao, Cuihua; Liu, Lingling; Liu, Yanli; Jiang, Lisheng; Zhang, Sijing; Chen, Xin; Jiang, Xinqing; Lan, Yue; Wei, Xinhua (Frontiers in Behavioral Neuroscience, 2019)
Theta burst stimulation (TBS) is a powerful variant of repetitive transcranial magnetic stimulation (rTMS), making it potentially useful for the treatment of swallowing disorders. However, how dose TBS modulate human swallowing cortical excitability remains unclear. Here, we aim to measure the after-effects of spontaneous brain activity at resting-state using the regional homogeneity (ReHo) approach in healthy subjects who underwent different TBS protocols over the suprahyoid muscle cortex. Sixty healthy subjects (23.45 +/- 2.73 years, 30 males) were randomized into three groups which completed different TBS protocols. The TMS coil was applied over the cortex of the suprahyoid muscles. Data of resting-state functional MRI (Rs-fMRI) of the subjects were acquired before and after TBS. The ReHo was compared across sessions (continuous TBS (cTBS), intermittent TBS (iTBS) and cTBS/iTBS) and runs (pre/post TBS). In the comparison between pre- and post-TBS, increased ReHo was observed in the right lingual gyrus and right precuneus and decreased ReHo in the left cingulate gyrus in the cTBS group. In the iTBS group, increased ReHo values were seen in the pre-/postcentral gyrus and cuneus, and decreased ReHo was observed in the left cerebellum, brainstem, bilateral temporal gyrus, insula and left inferior frontal gyrus. In the cTBS/iTBS group, increased ReHo was found in the precuneus and decreased ReHo in the right cerebellum posterior lobe, left anterior cerebellum lobe, and right inferior frontal gyrus. In the post-TBS inter-groups comparison, increased ReHo was seen in right middle occipital gyrus and decreased ReHo in right middle frontal gyrus and right postcentral gyrus (cTBS vs cTBS/iTBS). Increased ReHo was shown in left inferior parietal lobule and left middle frontal gyrus (cTBS vs iTBS). Increased ReHo was shown in right medial superior frontal gyrus and decreased ReHo in right cuneus (cTBS/iTBS vs iTBS). The results provide a novel insight into the neural mechanisms of TBS on swallowing cortex.